Make remote working work for you (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. The fact that 97.4% of respondents to Buffer's State of Work Survey who currently worked remotely wished to retain that option shows that the new flexibility afforded by working from home is a gamechanger. The problem is, we've not nailed it yet. 67% of those working remotely feel pressured to be available at all hours of the day, and 65% admitted to working longer hours than ever before. In this track, we aim to provide tips on how to create a clearer physical distinction in the home between work and leisure, as well as setting mental boundaries and clearly separating office hours from personal hours. Learning Objectives Learn how the pandemic has affected the employment landscape and how working from home has been a blessing and a curse for many Learn how to make your home an office and how to redress the work-life imbalance which is created when people feel they have to work harder and longer when working remotely.